2020
DOI: 10.1093/function/zqaa009
|View full text |Cite
|
Sign up to set email alerts
|

Fusion-Independent Satellite Cell Communication to Muscle Fibers During Load-Induced Hypertrophy

Abstract: Abstract The “canonical” function of Pax7+ muscle stem cells (satellite cells) during hypertrophic growth of adult muscle fibers is myonuclear donation via fusion to support increased transcriptional output. In recent years, however, emerging evidence suggests that satellite cells play an important secretory role in promoting load-mediated growth. Utilizing genetically modified mouse models of delayed satellite cell fusion and in vivo extracellular vesicle tracki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 146 publications
(181 reference statements)
5
63
0
Order By: Relevance
“…<3 months in mice), 2,4 but that alternative epigenetic mechanisms such as myonuclear DNA methylation, histone modifications, or miRNA expression could explain muscle memory in the long‐term after myonuclear number has stabilized 12,70,73,74 ( Figure 9). Furthermore, myoblasts are shown to have a long‐term epigenetic memory of previous exposure to stress in vitro 75 , so satellite cells could theoretically contribute to muscle memory in myofibers via recently identified fusion‐independent mechanisms in vivo 76 . Future studies may employ newly developed voluntary 77 or involuntary resistance training paradigms (exercise dosage can be controlled for in the latter) 78,79 for mice that can complement PoWeR (recently reviewed here 31 ) and will aim to address how myonuclei are removed during detraining, the role of myonuclear translocation during exercise adaptation, whether epigenetic changes could explain myonuclear shape transformations with training and detraining, which exercise‐induced epigenetic alterations to myonuclei are permanent, and how miR‐1 could facilitate retraining adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…<3 months in mice), 2,4 but that alternative epigenetic mechanisms such as myonuclear DNA methylation, histone modifications, or miRNA expression could explain muscle memory in the long‐term after myonuclear number has stabilized 12,70,73,74 ( Figure 9). Furthermore, myoblasts are shown to have a long‐term epigenetic memory of previous exposure to stress in vitro 75 , so satellite cells could theoretically contribute to muscle memory in myofibers via recently identified fusion‐independent mechanisms in vivo 76 . Future studies may employ newly developed voluntary 77 or involuntary resistance training paradigms (exercise dosage can be controlled for in the latter) 78,79 for mice that can complement PoWeR (recently reviewed here 31 ) and will aim to address how myonuclei are removed during detraining, the role of myonuclear translocation during exercise adaptation, whether epigenetic changes could explain myonuclear shape transformations with training and detraining, which exercise‐induced epigenetic alterations to myonuclei are permanent, and how miR‐1 could facilitate retraining adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…With mechanical loading-induced skeletal muscle hypertrophy, numerous lines of evidence across different species suggest that muscle fibers can adapt and grow appreciably without satellite cell fusion and myonuclear accretion (Murach et al, 2018a); however, long-term hypertrophy without satellite cells is attenuated concomitant with excess ECM accumulation (Fry et al, 2014a). Our laboratory recently showed that satellite cells may communicate with fibrogenic cells and muscle fibers (Murach et al, 2020c) via miRNA-containing extracellular vesicles (EVs) to regulate the muscle fiber milieu during hypertrophy. Presently, it is unclear whether early satellite cell-mediated secretory signaling throughout muscle is sufficient for long-term adult muscle hypertrophy or whether myonuclear addition is required to sustain hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…The canonical function of SCs during hypertrophic response of adult myofibers is myonuclear accretion via cells fusion. Nevertheless, Murach et al underlined that SCs also display fusion-independent roles through their secretory functions, showing that SCs communicate with muscle fibers without necessarily achieve fusion [ 233 ]. They previously demonstrated that SCs communicated with fibrogenic cells through exosomes to ensure correct regulation of the extracellular environment in response to hypertrophic stimuli [ 234 ].…”
Section: Implication Of Satellite Cells and Myonuclear Accretionmentioning
confidence: 99%
“…This fusion-independent mechanism probably involves miRNAs that affect extracellular matrix [ 234 ]. Using a mice model of delayed SCs fusion, authors provided evidence that SCs also released extracellular vesicles to muscle fibers [ 233 ]. From their results, authors gave novel insights about SCs functions during hypertrophy.…”
Section: Implication Of Satellite Cells and Myonuclear Accretionmentioning
confidence: 99%